Camrelizumab for relapsed or refractory classical Hodgkin lymphoma: Extended follow‐up of the multicenter, single‐arm, Phase 2 study. Issue 6 (5th November 2021) - Wu, Jianqiu; Song, Yuqin; Chen, Xinchuan; Lin, Tongyu; Cao, Junning; Liu, Yanyan; Zhao, Yaozhong; Jin, Jie; Huang, Haiwen; Hu, Jianda; Luo, Jun; Zhang, Liling; et al.
Abstract: Camrelizumab (a humanized high‐affinity IgG4 mAb against programmed death‐l) showed potent antitumor activity, well tolerance and controllable safety in patients with relapsed or refractory classical Hodgkin lymphoma (r/r cHL), based on the primary analysis of a Phase 2 study. Here, we present the extended follow‐up outcomes. Seventy‐five patients who had failed to achieve a remission or experienced progression after autologous stem cell transplantation or had received at least two lines of systemic chemotherapies were enrolled to receive camrelizumab 200 mg every 2 weeks. With a median follow‐up of 36.2 months (range, 7.2‐38.1), objective response rate per independent central review was 76.0% (95% confidence interval [CI],  64.7‐85.1). Among the 57 responders, 31 (54.4%) had ongoing responses. Median duration of response was 31.7 months (95% CI,  16.7‐not reached). Median progression‐free survival was 22.5 months (95% CI, 14.7‐not reached). Thirty‐six‐month overall survival rate was 82.7% (95% CI, 72.0‐89.5). Reactive capillary endothelial proliferation (RCEP) occurred in 97.3% of patients (73/75), but all RCEP were Grade 1 or 2 in severity and 67.1% of these patients (49/73) achieved complete resolution. Occurrence of new RCEP lesions was rare (8/42 [19.0%] at 12 months; 2/32 [6.3%] at 24 months). No treatment‐related deaths occurred, and no new toxicities were reported. With extended follow‐up, camrelizumab monotherapy continues to provide a robust and durable response, long survival and manageable safety in r/r cHL patients. Abstract : What's new? In an earlier phase 2 study, the PD‐1 inhibitor camrelizumab showed strong antitumor activity and a good safety profile in patients with relapsed or refractory classical Hodgkin's lymphoma (r/r cHL). Here, the authors report the results of a 3‐year follow up study. In the study, patients received 200 mg camrelizumab every two weeks. Of the 75 patients enrolled, 57 (76%) responded to the therapy, and 31 had ongoing responses. There were no treatment‐related deaths or new toxicities. Overall survival at 36 months was 82.7%. Camrelizumab appears to have a durable response in patients with r/r cHL.